Distinct Incidence of Takotsubo Syndrome Between Amyotrophic Lateral Sclerosis and Synucleinopathies: A Cohort Study - Izumi, Yuishin; Miyamoto, Ryosuke; Fujita, Koji; Yamamoto, Yuki; Yamada, Hirotsugu; Matsubara, Tomoyasu; Unai, Yuki; Tsukamoto, Ai; Takamatsu, Naoko; Nodera, Hiroyuki; Hayashi, Shinya; Oda, Masaya; et al. (Frontiers in Neurology, 2018)
Takotsubo syndrome (TTS) is an acute cardiac syndrome characterized by regional left ventricular dysfunction with a peculiar circumferential pattern, which typically results in apical ballooning. Evidence indicates a pivotal role of catecholamines in TTS, and researchers have discussed multiple hypotheses on the etiology, including multivessel coronary spasm, myocardial stunning, excessive transient ventricular afterload, and cardiac sympathetic overactivity with local noradrenaline spillover. Although central nervous system disorders, such as stroke and epilepsy, are known to trigger TTS, the incidence and clinical features of TTS in neurodegenerative disorders are poorly understood. Here, we retrospectively examined TTS cases in a single-center cohort composed of 250 patients with amyotrophic lateral sclerosis (ALS) and 870 patients with synucleinopathies (582 patients with Parkinson’s disease (PD), 125 patients with dementia with Lewy bodies (DLB), and 163 patients with multiple system atrophy (MSA)) and identified 4 (1.6%, including 2 women) cases with ALS and no cases with synucleinopathies. Two ALS patients underwent autopsy and the pathological findings were compatible with the chronological changes identified in catecholamine-induced cardiomyopathy. A literature review identified 16 TTS cases with ALS, 1 case each with PD and DLB, and no cases with MSA. When current and previous TTS cases with ALS were concatenated: 55% (11/20) were female; 35% (7/20) had a bulbar-onset and 45% (9/20) had a limb-onset; the mean age of TTS onset was 63.3±9.0 years and the mean interval time from ALS onset to TTS development was 4.9±3.0 years; no (0/16) patients developed TTS within 12 months after ALS onset; 50% (10/20) underwent artificial ventilations; the mortality was 17% (3/18); and most cases had precipitating factors, and TTS development was associated with gastrostomy, tracheostomy, or infections in 45% (9/20) of the patients. This study demonstrated that ALS is a considerable predisposing factor of TTS and that synucleinopathies rarely cause TTS. The distinct TTS incidence between ALS and synucleinopathies may be due to cardiac sympathetic overactivity in ALS and may also be affected by cardiac sympathetic denervation in synucleinopathies. Moreover, the etiology of TTS in ALS may be reasonably explained by the two-hit theory.